Biomechanical Evaluation of Capsulotomy and Capsular Repair in the Hip: Restoring Stability - Wuerz, Thomas H. (Orthop J Sports Med, 2015)
OBJECTIVES: The use of hip arthroscopy has increased over recent years to treat various forms of hip pathologies including femoroacetabular impingement. While a capsulotomy facilitates adequate visualization and access for diagnostic and interventional purposes, the current literature remains divided over the use of routine capsular closure to address the iatrogenic instability that may be induced by an excessive or unclosed capsulotomy. The purpose of this biomechanical study was to determine if hip capsulotomy creates significant alterations in rotational range of motion and stability measures. Additionally, does a capsular repair return these variables to normal? METHODS: Eight fresh-frozen cadaveric hip specimens consisting of the hemipelvis, femur, and overlying soft tissues were used for this study. All specimens were screened by computed tomography (CT) to assess for the absence of significant bony pathology. Each hip was then tested under torsional loads of 6 N·m applied via a pulley system in conjunction with a vertical force exerted by a servohydraulic frame. Conditions tested were as follows: 1) neutral flexion with the capsule intact 2) neutral flexion with a 4 cm inter-portal capsulotomy 3) neutral flexion with a 6 cm inter-portal capsulotomy 4) neutral flexion with capsulotomy repair. Soft tissue was retained during all interventions. Range of motion (from external to internal rotation), hysteresis area, and neutral zones were the outcome measures for stability obtained in each condition. RESULTS: While the data demonstrated a positive and statistically significant correlation between the sizes of the capsulotomy and measures of joint instability (range of motion (ROM), hysteresis area, and neutral zone), no significant differences were seen between the intact and repaired hips with regards to such measures (Table). Larger size capsulotomies were accompanied by significant increases in all three measures of joint instability while the repair effectively restored the capsule to conditions similar to its intact state. CONCLUSION: To the best of the authors’ knowledge, this study is the first to demonstrate the biomechanical consequences of sequentially increasing capsulotomy incisions and their repair on a hip joint that still contains its surrounding soft tissue. The results of this study not only confirm the notion of introducing iatrogenic joint instability with larger sized capsulotomies, but also propose the complete capsular closure as an appropriate solution.